BF4 – Tailoring Solvation Chemistry of Ether-Based Electrolytes to Construct Stable Electrode/Electrolyte Interfaces for Sodium-Ion Full Batteries - Yi, Xiaoli; Li, Xinhai; Zhong, Jing; Cui, Zhuangzhuang; Wang, Zhixing; Guo, Huajun; Wang, Jiexi; Yan, Guochun (ACS applied materials & interfaces, 2024)
The ether-based electrolytes show excellent performance on anodes in sodium-ion batteries (SIBs), but they still show poor compatibility with the cathodes. Here, ether electrolytes with NaBF4 as the main salt or additive were applied in NFM//HC full cells and showed enhanced performance than the electrolyte with NaPF6. Then, BF4 – was found to have a stronger interaction with Na+, which could reduce the solvation of Na+ with the solvent, thus inducing the formation of the cathode electrolyte interface (CEI) and solid electrolyte interface (SEI) layers rich in inorganic species. Moreover, the morphology, structure, composition, and solubility of CEI and SEI were explored, concluding that NaBF4 could induce more stable CEI and SEI layers rich in B-containing species and inorganics. This work proposes using NaBF4 as the main salt or additive to improve the performance of ether electrolytes in NFM//HC full cells, which provides a strategy to improve the compatibility of ether-based electrolytes and cathodes.